Proposed Remedies to Prevent Road Traffic Accidents (RTAs) on Highways in Pakistan - Detho, A.; Samo, S. R.; Mukwana, K. C.; Memon, I. A.; Rajput, U. A. (Engineering, Technology & Applied Science Research, 2018)
In Pakistan, the number of roads and highways is increasing along with the number of road traffic accidents (RTAs). Many researchers attempted to collect data of RTAs and to investigate their causes. Keeping those causes and reasons for RTAs in mind, remedies to prevent RTAs on the highways in Pakistan are proposed to make the roads and highways safer for traveling.